Sosialisasi Program Penyiraman Tanaman Hias Secara Otomatis Berbasis Arduino - Sufaidah, Siti; Lilawati, Emi; Arya Dinta, Firda; Khofifah, Khofifah; Wijanarko, Eko Bayu; Cahyaningtyas, Dhita (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2024)
Janti Village is a village in Mojoagung sub-district with a population of around 3,570 people. The Janti village community has a variety of potential, especially in the agricultural and crafts sectors. The women in Janti village have an interest and hobby in planting ornamental plants in front of the house. These ornamental plants are an important part of the beauty and aesthetics of their environment. Even though they have a great love and interest in ornamental plants, they often face several obstacles in caring for these plants. One of the main obstacles is their busy daily lives. The community service team consisting of lecturers and students offers collaboration on developing an automatic watering tool, namely an Adruino-based ornamental plant watering tool. The method used is socialization and practicing how to use automatic watering tools. With this system, we hope to provide concrete benefits to the people of Janti Village, improve their quality of life, and utilize technology to support daily activities